2019
DOI: 10.1111/crj.13059
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal noninvasive prediction of pulmonary hypertension in IPF

Abstract: Introduction and Objective Pulmonary hypertension (PH) complicating idiopathic pulmonary fibrosis (IPF) is challenging to diagnose given inaccuracy of transthoracic echocardiogram (TTE) measurements. However, it has significant prognostic implications and is therefore important to accurately identify. Methods We conducted a cross‐sectional study of patients with IPF who underwent RHC as part of their evaluation. A variety of commonly available noninvasive variables were evaluated for their ability to predict p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 29 publications
(47 reference statements)
0
25
0
Order By: Relevance
“…32 Multiple studies have demonstrated that patients with PH‐ILD have a lower 6MWD than ILD patients without PH. 10 , 11 , 13 , 19 , 33 Not only does a reduced 6MWD suggest the diagnosis of concomitant PH in ILD patients, but it is also associated with decreased survival. 2 However, there is conflicting data demonstrating that shorter distances on a 6MWT were actually not predictive of PH in ILD.…”
Section: Discussionmentioning
confidence: 99%
“…32 Multiple studies have demonstrated that patients with PH‐ILD have a lower 6MWD than ILD patients without PH. 10 , 11 , 13 , 19 , 33 Not only does a reduced 6MWD suggest the diagnosis of concomitant PH in ILD patients, but it is also associated with decreased survival. 2 However, there is conflicting data demonstrating that shorter distances on a 6MWT were actually not predictive of PH in ILD.…”
Section: Discussionmentioning
confidence: 99%
“…In human medicine, the gold standard to diagnose an increase in pulmonary arterial pressure is right heart catheterization (24). In veterinary medicine, this technique is not commonly used and echocardiography remains the method of choice to diagnose PH (15).…”
Section: Discussionmentioning
confidence: 99%
“…An interesting study of 105 patients with idiopathic pulmonary fibrosis (IPF) revealed that the ratios FVC/DLCO (forced vital capacity/diffusion capacity) and diameters of pulmonary artery/aorta were useful adjuncts to sPAP to predict PH in a linear regression model (R 2 ¼0.39). 25 Another small study (n ¼ 61) with IPF patients regressed FVC/DLCO and resting pulse oximetry with PA mean as a continuous variable (R 2 ¼0.55). 26 Whether these models are reliable in cardiological patients without lung disease is unclear.…”
Section: Discussionmentioning
confidence: 99%